2007
DOI: 10.1111/j.1537-2995.2006.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cell lines stably expressing HNA‐1a, ‐1b, and ‐2a antigen with low background reactivity in flow cytometric analysis

Abstract: These results indicate that the K562 panel cell lines provide a good panel for detecting HNA-reactive neutrophil antibodies in human serum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…1. KY-HNA-1a cells were established by transducing the HNA-1a gene with a retrovirus vector to confer stable transgene expression in K562 cells that exhibited low background reactivity to human serum samples obtained from healthy donors, as described earlier [7]. The KY-MAIGA system for HNA-1a Abs detection based on KY-HNA-1a panel whole blood of HNA-1a/a was used as a neutrophil source.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. KY-HNA-1a cells were established by transducing the HNA-1a gene with a retrovirus vector to confer stable transgene expression in K562 cells that exhibited low background reactivity to human serum samples obtained from healthy donors, as described earlier [7]. The KY-MAIGA system for HNA-1a Abs detection based on KY-HNA-1a panel whole blood of HNA-1a/a was used as a neutrophil source.…”
Section: Serum Samplesmentioning
confidence: 99%
“…However, conventional neutrophil-based tests have two further drawbacks: firstly, a typed panel of neutrophils is required; secondly, the presence of other leukocyte antibodies, such as human leukocyte antigen (HLA) Abs, may affect the detection of HNA Abs. To overcome these drawbacks, we developed panel cell lines (so-called KY cells) capable of stably expressing HNA antigens and established KY cell-based IFT (KY-IFT) [7][8][9]. We have been using these two detection systems in combination to detect HNA Abs in transfusion reaction cases and neutropenia patients for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yasui et al [4] reported the establishment of gene transfected K562 cell lines that express HNA-1a, -1b, or -2a antigens. Later on, they established new cell lines that selectively express HNA-1c, -4a, -4b, -5a, or -5b antigens [5].…”
Section: Discussionmentioning
confidence: 99%
“…Currently MAIGA is a laborious and time-consuming test, not suitable for antibody screening and rarely used in routine practice. Moreover it seems that GIFT is more sensitive than MAIGA [Bruin et al 2005], and consequently since new techniques such as mixed passive hemagglutination [Han et al 2006], transfected cell lines expressing neutrophil antigens [Yasui et al 2007[Yasui et al , 2008Woźniak et al 2012], soluble recombinant HNA production by transfection of insect cells [Bayat et al 2009;Werth et al 2013] or the microbead test [Fromont et al 2010] have not yet definitely proved their efficacy or are not yet commercially available, the majority of laboratories worldwide analyse patient sera by the flow cytometry assay.…”
Section: Diagnosismentioning
confidence: 99%